Suspecting Lupus by Analyzing Rashes using Artificial Neural Networks (ANN) - Saha, Payel; Mandal, Rakesh Kumar (International Journal of Computer Sciences and Engineering, 2025)
In this research paper lupus disease is suspected using Artificial Neural Networks (ANN). Lupus is a chronic disease which is not curable. But it can be controlled by early diagnosis. By analyzing various symptoms it is very difficult to diagnose lupus manually. This paper is an approach to diagnose lupus in an efficient way with the help of ANN. An ANN has been designed here to suspect lupus. The ANN consists of many neurons associated with weights. Each neuron represents each symptom. Here patients are classified into two categories: infected and non-infected. Classification is an important tool in medical diagnosis. The data was collected from North Bengal Medical College for training the net